Brésil: les territoires de la question agraire - Girardi, Eduardo Paulon [UNESP]; Fernandes, Bernardo Mançano [UNESP] (My University, 2006)
This paper presents a territorial analysis of the Brazilian agrarian question. Mapping and graphic modelling were used simultaneously to analyse the territory and agribusiness, and the peasantry and the struggle for land, and their relationship to Brazil's agropastoral frontier.
Brazilian: Territories of the agrarian question
Keywords: Agrarian question; Amazonia; Brazil; agroindustry; mapping; modeling; territory; South America